2018
DOI: 10.1109/tcsi.2017.2754342
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Source Capacitance and Inductance on $N$ -Path Mixers and Filters

Abstract: Switch-R-C passive N-path mixers and filters enable interference-robust radio receivers with a flexibly programmable center frequency defined by a digital multi-phase clock. The radio frequency (RF) range of these circuits is limited by parasitic shunt capacitances, which introduce signal loss and degrade noise figure. Moreover, the linear periodically time varying (LPTV) nature of switch-R-C circuits results in unwanted signal folding which needs to be suppressed by linear time-invariant (LTI) pre-filtering b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…It is observed that both the gain and optimum S 11 dip are shifted towards lower frequencies due to the presence of s , in agreement with the analysis in [13,21]. This issue can be addressed by introducing complex feedback with resistors [3] or adding a series inductor [21]. The measured gain is about 16 dB and the −3dB,BPF is about 13 MHz ( −3dB,BB =6.5 MHz), while the filter roll-off from 20 to 200-MHz offset is about -32 dB (-34 dB from (6)) for the upper sideband, and -33 dB (-38 dB from (6)) for the lower sideband.…”
Section: A Gain and S11supporting
confidence: 89%
See 1 more Smart Citation
“…It is observed that both the gain and optimum S 11 dip are shifted towards lower frequencies due to the presence of s , in agreement with the analysis in [13,21]. This issue can be addressed by introducing complex feedback with resistors [3] or adding a series inductor [21]. The measured gain is about 16 dB and the −3dB,BPF is about 13 MHz ( −3dB,BB =6.5 MHz), while the filter roll-off from 20 to 200-MHz offset is about -32 dB (-34 dB from (6)) for the upper sideband, and -33 dB (-38 dB from (6)) for the lower sideband.…”
Section: A Gain and S11supporting
confidence: 89%
“…The receiver conversion gain obtained from the RLC model can be computed by using (6) and 7, while p of (6) becomes p (ω LO )||( ω s ) −1 now. It is observed that both the gain and optimum S 11 dip are shifted towards lower frequencies due to the presence of s , in agreement with the analysis in [13,21]. This issue can be addressed by introducing complex feedback with resistors [3] or adding a series inductor [21].…”
Section: A Gain and S11supporting
confidence: 81%
“…Similarly, the peak gain frequency will also shift to the left of LO due to parasitic capacitance. However the amount of frequency shift is governed by the transfer function and it is different from the S 11 shift [32]. Both shifts can be compensated using complex feedbacks [6], though not implemented here.…”
Section: A Gain S11 and Nfmentioning
confidence: 99%
“…Now, the expression presented in (21) can be described as V out,X,0 (f ) can be solved by setting τ d to zero in Equation (25). By using (5) and (17), the frequency response of the filter is calculated by…”
Section: Effect Of Energy Sharing Between Adjacent Baseband Capacitorsmentioning
confidence: 99%
“…This paper likewise 24,25 proposes a simple analytical method to calculate the frequency responses of N-path circuits by means of impulse response. However, this paper uses impulse response of circuit driven by delayed clock, and Pavan and Klumperink 24,25 use adjoint network and SFG to calculate the transfer function. The method may also be used for sample-and-hold circuit.…”
mentioning
confidence: 99%